2016
DOI: 10.5935/medicalexpress.2016.02.07
|View full text |Cite
|
Sign up to set email alerts
|

Goal-directed therapy for decompensated heart failure and renal dysfunction. A pilot randomized clinical trial

Abstract: OBJECTIVES:Acute heart failure is associated with low cardiac output syndrome and renal dysfunction. However, it is not known whether a goal-directed protocol guided by tightly controlled hemodynamic variables, including pulmonary artery catheter, will safely improve clinical renal dysfunction markers in these patients when compared to a less invasive approach. METHODS: Pilot, randomized clinical trial aimed at patients with known heart failure, low cardiac output syndrome and renal dysfunction with less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
0
3
1
3
Order By: Relevance
“…However, despite lesser fluid in the GDT group, Bastos's study showed no difference in in-hospital stay of both groups. 21 In the present study, the amount of fluid used in the standard group was higher. The Bastos study 21 observed this on the first day after surgery.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…However, despite lesser fluid in the GDT group, Bastos's study showed no difference in in-hospital stay of both groups. 21 In the present study, the amount of fluid used in the standard group was higher. The Bastos study 21 observed this on the first day after surgery.…”
Section: Discussioncontrasting
confidence: 43%
“…Maintaining cardiac output was compensated by inotropy instead of increasing fluid intake, and ultimately patients' outcomes were better, and hospital stays were reported to be shorter. In Bastos's study, 21 the dose of inotropic (dobutamine) was the same in both groups. In our study, the number of blood products received was also recorded and evaluated, which showed a significant difference only in the case of platelets.…”
Section: Discussionmentioning
confidence: 89%
“…Perfil do resumo da amostra encontrada conforme variáveis utilizadas para análise das publicações localizadas nas bases de dados online. 1,2,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19 aferido em numerosas situações clínicas, cirúrgicas e experimentais. Para sua realização, utiliza-se um CVC aplicado preferencialmente na veia jugular.…”
Section: Obteve-se Como Resultado 169 Publicações (Tabela 1) a Partiunclassified
“…Para sua realização, utiliza-se um CVC aplicado preferencialmente na veia jugular. 9 A medida da PVC é um dos primeiros passos na avaliação da volemia e da função cardíaca de pacientes graves. A PVC pode contribuir para avaliação e controle do estado do volume intravascular.…”
Section: Obteve-se Como Resultado 169 Publicações (Tabela 1) a Partiunclassified
“…Atribui-se essa diferença ao maior engajamento das mulheres em ações preventivas e de controle de saúde, adoção de hábitos de vida mais saudáveis, ao contrário dos homens que se caracterizam pela busca tardia ao serviço de saúde e por terem um estilo de vida de maior risco cardiovascular apresentando-se muitas vezes em estágios descompensados e/ou mais avançados de IC. Estes aspectos não foram alvo deste estudo (BRASIL, 2008;PILGER;MENON;MATHIAS, 2011;BASTOS, 2016;DE ALMEIDA NETO et al, 2016, AHMETI et al, 2017.…”
Section: Características Socioeconômicasunclassified